Arterial Transluminal dilatation, our experience - Grinfeld, Liliana; Grinfeld, David; Grinfeld, Roberto; Belardi, Jorge; Pastene, Ricardo (Cirugía del Uruguay, 1983)
The authors expose their experience with arterial transluminal dilatation. At vascular peripherical level they performed this procedure in 26 oportunities with 100º/o of succes at iliac leve! where they get the best results. Coronary transluminal angiopastia was performed in 21 cases with good results in anter ior descendente coronaris di latation. No mortality was recorded with this procedure.